2016
DOI: 10.1177/1457496916665542
|View full text |Cite
|
Sign up to set email alerts
|

Greater Success of Primary Fascial Closure of the Open Abdomen: A Retrospective Study Analyzing Applied Surgical Techniques, Success of Fascial Closure, and Variables Affecting the Results

Abstract: Most of the open abdomen patients (72.1%) underwent fascial defect repair during the primary hospitalization, and 70.5% of them underwent direct fascial closure. Negative pressure wound therapy was used as a temporary closure method for 86.9% of the patients. Negative pressure wound therapy combined with mesh-mediated medial traction resulted in the shortest open abdomen time (p = 0.039) and the highest fascial repair rate (p = 0.000) compared to negative pressure wound therapy only or no negative pressure wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Regarding the closure of an open abdomen, both the synthetic mesh-mediated fascial traction in combination with NPT has been advocated, with currently the best outcomes reported, as well as the use of (resorbable) meshes as an adjunct to primary fascial closure during OA management. Four observational studies ( 33 36 ) reported on using mesh at the time of primary fascial closure. Regarding the presence of an incisional hernia, all together, 98 patients were studied with an incidence of incisional hernias of around 20%.…”
Section: Prevention Of Incisional Hernia Development After Oa Managemmentioning
confidence: 99%
“…Regarding the closure of an open abdomen, both the synthetic mesh-mediated fascial traction in combination with NPT has been advocated, with currently the best outcomes reported, as well as the use of (resorbable) meshes as an adjunct to primary fascial closure during OA management. Four observational studies ( 33 36 ) reported on using mesh at the time of primary fascial closure. Regarding the presence of an incisional hernia, all together, 98 patients were studied with an incidence of incisional hernias of around 20%.…”
Section: Prevention Of Incisional Hernia Development After Oa Managemmentioning
confidence: 99%
“…Eleven articles were included for qualitative synthesis. Complementary data from three studies [8,12,13] was collected after correspondence. Since no RCTs comparing VAWCM with other TAC techniques were identified, there was no basis on which to perform a meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In 2007, the first report of a modified technique combining vacuum-assisted wound closure with mesh-mediated fascial traction (VAWCM) for long-term therapy of the open abdomen was published [5]. Since then, several centres have adopted this technique and reported their experiences [6][7][8][9][10][11][12][13][14][15]. The aim of this systematic review was to report the short-term and long-term results for the VAWCM technique.…”
mentioning
confidence: 99%
“…Of the 15 articles included, 6 were prospective (3, 9-13) and 9 were retrospective (2,(14)(15)(16)(17)(18)(19)(20)(21). No study was randomized, and most studies were observational with only one treatment group.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…No study was randomized, and most studies were observational with only one treatment group. Four reports (15,18,19,21) included other techniques beside VAWCM, from which the VAWCM results were extracted. The study populations ranged between 7 and 111 with a mean of 40, and 600 patients were totally included (2, 3, 9-21).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%